Harian Rakjat “Mengangkat” Suara Dari Bawah: Rubrik Asmu Menjawab Dalam Memberitakan Suara Petani Terkait Kasus Landreform 1961-1965 - Bambang Rakhmanto (Indonesian Historical Studies, 2018)
This article discusses the role of Harian Rakjat to established public opinion via citizen journalists. It aimed to seek sympathy from the peasants when implemented land-reform policies as stipulated in the Basic Agrarian Law (UUPA). The discussion was carried out by examining the articles of the resident that reviewed responded the issue of land ownership in the column of Asmu Menjawab. By using the historical method and applying discourse analysis theory, this study succeeded to find the implementation of land reform policies reaped many pros and cons among the community. The implementation of land reform in Java according to the testimonies was then used by the Indonesian Communist Party (PKI) as political propaganda in its practical politics.